HIBRIDITAS, MIMIKRI, DAN AMBIVALENSI DALAM BUKU KUMPULAN CERPEN BERBURU BUAYA DI HINDIA TIMUR KARYA RISDA NUR WIDIA - Bella Berliana; Diah Rahma Cahya Agustyowati (Universitas Muhammadiyah Surakarta, 2023)
The purpose of this study is to describe the forms of hybridity, mimicry, and ambivalence that are presented in the book collection of short stories Berburu Buaya di Hindia Timur by Risda Nur Widia. This research is classified as a qualitative descriptive study with a postcolonial approach. The data collection technique used is qualitative analysis of literary works documents. The data analysis process is carried out through three stages, namely: (1) data reduction, selecting the data that has been collected and classifying it into predetermined categories; (2) presenting data, describing and analyzing each data; and (3) conclusion, giving a conclusion to the data that has been analyzed. The results show that there are seven forms of hybridity which include: (1) language, (2) education, (3) mindset, (4) belief, (5) court system, (6) lifestyle, and (7) lifestyle tools. . Furthermore, five forms of mimicry were also found which include: (1) means of payment, (2) the tax system, (3) weapons, (4) naming places, and (5) cooking spices. Meanwhile, there are two forms of ambivalence, namely: (1) concubines and (2) looks.Keywords: hybridity, mimicry, ambivalence, postcolonialism